Inter-specialty variation of the Press Ganey Outpatient Medical Practice Survey. Issue 12 (26th March 2021) - Stephens, Andrew R.; Presson, Angela P.; Chen, Danli; Tyser, Andrew R.; Kazmers, Nikolas H.
Abstract : Abstract: Measuring patient satisfaction scores and interpreting factors that impact their variation is of importance as scores influence various aspects of health care administration. Our objective was to evaluate if Press Ganey scores differ between medical specialties. New patient visits between January 2014 and December 2016 at a single tertiary academic center were included in this study. Press Ganey scores were compared between specialties using a multivariable logistic mixed effects model. Secondary outcomes included a comparison between surgical versus non-surgical specialties, and pediatric versus adult specialties. Due to the survey's high ceiling effect, satisfaction was defined as a perfect total score. Forty four thousand four hundred ninety six patients met inclusion criteria. Compared to internal medicine, plastic surgery, general surgery, dermatology, and family medicine were more likely to achieve a perfect overall score, as, with odds ratios of 1.46 ( P = .02), 1.29 ( P = .002), 1.22 ( P = .004), and 1.16 ( P = .02) respectively. Orthopaedics, pediatric medicine, pediatric neurology, neurology, and pain management were less likely to achieve satisfaction with odds ratios of 0.85 ( P = .047), 0.71 ( P < .001), 0.63 ( P = .005), 0.57 ( P < .001), and 0.51 ( P = .006), respectively. Compared to pediatric specialties, adult specialties were more likely to achieve satisfaction (OR 1.73; P < .001). There were no significant differences between surgical versus non-surgical specialties. Press Ganey scores systematically differ between specialties within the studied institution. These differences should be considered by healthcare systems that use patient satisfaction data to modify provider reimbursement.